Healthcare resource utilization and costs associated with first-line ibrutinib compared to chemoimmunotherapy treatment among Medicare beneficiaries with chronic lymphocytic leukemia. (1st December 2020) - Huang, Qing; Emond, Bruno; Lafeuille, Marie-Hélène; Gupta, Deepshekhar; Lefebvre, Patrick; Sundaram, Murali; Mato, Anthony
Abstract: Objective: This retrospective observational study aimed to compare healthcare resource utilization and costs of Medicare beneficiaries with chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL) who received ibrutinib versus chemoimmunotherapy (CIT) in first line (1 L). Methods: Fee-for-service (FFS) and Medicare Advantage (MA) claims data were used to identify adults with a CLL/SLL diagnosis initiating 1 L ibrutinib single agent or CIT between 4 March 2016 and 30 September 2017 (index date). HRU and costs (Medicare spending) were evaluated during 1 L Oncology Care Model (1 L OCM) episodes (the first six months post-index) and over the observed 1 L duration. Patients' baseline characteristics were balanced using inverse probability of treatment weighting. Mean monthly cost differences (MMCDs) obtained from ordinary least square regressions were used to compare costs between ibrutinib and CIT cohorts. Results: In the Medicare FFS dataset (ibrutinib: n  = 2014; CIT: n  = 2050), ibrutinib patients incurred significantly higher monthly pharmacy costs (1 L OCM: MMCD = $4878, p  < .0001; 1 L duration: MMCD= $4892, p  < .0001) that were fully offset by lower monthly medical costs (1 L OCM: MMCD= -$8289, p  < .0001; 1 L duration: MMCD=-$5888, p  < .0001), yielding a monthly total healthcare cost reduction (1 L OCM: MMCD=-$3411, p  < .0001; 1 L duration: MMCD=-$996, p  < .0001) relative to CIT patients. In the MA dataset (ibrutinib: n  = 293; CIT: n  = 303), ibrutinib was also associated with a monthly total healthcare cost reduction (1 L OCM: MMCD=-$10, 459; 1 L duration: MMCD=-$5492). Conclusions: In Medicare patients with CLL/SLL, 1 L ibrutinib single agent was associated with total monthly cost savings relative to 1 L CIT, driven by lower monthly medical costs that fully offset higher monthly pharmacy costs.